Exploring the Role of Psychosocial Factors in Medication Compliance among Gonorrhea Patients - Maler, Tangge; Hamdi, Sintiya; Manalu, Putranto; Girsang, Ermi; Suhartina (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Gonorrhea is a globally prevalent sexually transmitted infection (STI) that continues to present a serious public health challenge, particularly in light of the increasing threat of antimicrobial resistance. Effective disease management depends significantly on patient adherence to prescribed treatments. However, suboptimal adherence is frequently reported, which undermines control efforts and contributes to the emergence of drug-resistant Neisseria gonorrhoeae strains. Purpose: This study aimed to identify factors influencing medication adherence among patients diagnosed with gonorrhea. Methods: A cross-sectional study was conducted involving 74 participants. Data were collected through structured questionnaires assessing five variables: knowledge of gonorrhea, family support, perceived stigma, self-efficacy, and treatment adherence. Univariate analysis using descriptive statistics was performed to summarize demographic characteristics and key variables. Chi-square tests were used to determine the association between predictor variables and treatment adherence. Results: The findings showed that 86.5% of participants had good knowledge regarding gonorrhea, while 56.6% reported insufficient family support. Most respondents (81.1%) did not experience perceived stigma, and 64.9% reported high self-efficacy. Overall, 64.9% of participants adhered to their treatment regimen. Bivariate analysis revealed significant associations between treatment adherence and knowledge (p = 0.007; OR = 6.111), family support (p = 0.008; OR = 4.821), perceived stigma (p = 0.001; OR = 7.571), and self-efficacy (p = 0.001; OR = 7.200). Conclusion: The results underscore the importance of psychosocial factors in enhancing medication adherence. Targeted interventions addressing knowledge, family support, stigma, and self-efficacy are essential to improving treatment outcomes and reducing gonorrhea transmission.